(untitled) - Hyams, Ross. (New York,South Melbourne, Vic., 2004)
This updated second edition is organised around a series of exercises that teach skills by simulating real-life legal situations. It also addresses the ethics of legal practice, highlighting the professional duties of lawyers and discussing the ethical decisions that lawyers must frequently make. Practical Legal Skills is designed for all those engaged in legal training, including undergraduates, graduates, and practising lawyers undertaking in-house training.
Keywords: Thỏa thuận pháp lý,Legal composition,Thực hành luật,Practice of law; Úc,Australia